The denominator( s ) we are given are
, and . The first thing we want to do is factor the expressions, to make this easier -
![x^2 + 4x + 4](https://tex.z-dn.net/?f=x%5E2%20%2B%204x%20%2B%204)
This expression is a perfect square, as ( x )^2 = x^2, ( 2 )^2 = 4, 2 * ( x ) * ( 2 ) = 4x. Thus, the simplified expression should be the following -
![( x + 2 )^2](https://tex.z-dn.net/?f=%28%20x%20%2B%202%20%29%5E2)
The other expression is, on the other hand, not a perfect square so we must break this expression into groups and attempt factorization -
![x^2 + 5x + 6,\\\left(x^2+2x\right)+\left(3x+6\right),\\x\left(x+2\right)+3\left(x+2\right),\\\left(x+2\right)\left(x+3\right)\\\\Factored Expression = \left(x+2\right)\left(x+3\right)](https://tex.z-dn.net/?f=x%5E2%20%2B%205x%20%2B%206%2C%5C%5C%5Cleft%28x%5E2%2B2x%5Cright%29%2B%5Cleft%283x%2B6%5Cright%29%2C%5C%5Cx%5Cleft%28x%2B2%5Cright%29%2B3%5Cleft%28x%2B2%5Cright%29%2C%5C%5C%5Cleft%28x%2B2%5Cright%29%5Cleft%28x%2B3%5Cright%29%5C%5C%5C%5CFactored%20Expression%20%3D%20%5Cleft%28x%2B2%5Cright%29%5Cleft%28x%2B3%5Cright%29)
Combining ( x + 2 )^2 and ( x + 2 )( x + 3 ), the expression that contains factors of each is ( x + 2 )^2 * ( x + 3 ), or in other words the LCM.
<u><em>Solution = </em></u>
<u><em /></u>
It represents the first one 3+(-1)
Answer: 195
Step-by-step explanation: Well first you would do 165 divided by 11 to find the rate. Then multiply what you got as your rate by 13. Then you would get 195.
Step-by-step explanation:
slope= -1/2
y intercept= 2
y=mx+b
m is the slope and b is the y intercept.